Adherence to medication, physical activity and diet among older people living with diabetes mellitus: Correlation between cognitive function and health literacy. (December 2020) - Crespo, Thaísa Soares; Andrade, João Marcus Oliveira; Lelis, Deborah de Farias; Ferreira, Alice Crespo; Souza, João Gabriel Silva; Martins, Andréa Maria Eleutério de Barros Lima; Santos, Sérgio Henrique Sousa
Abstract: Background: Diabetes mellitus (DM) is a public health problem, which requires enhanced self-care in order to avoid complications. However, cognitive impairment can reduce these abilities and may affect health literacy (HL) of patients in terms to understand and apply information. Therefore, this study evaluated the correlation between cognitive condition and HL related to medication adherence, physical activity and nutritional status among people living with DM. Methods: A cross-sectional study was carried out among elderly people (≥ 60 years old) with DM. The cognitive condition was evaluated using the Mini-Mental State Examination (MMSE) and the HL using the following questionnaires: Literacy Assessment for Diabetes (LAD-60), Nutritional Literacy among People with Diabetes (NLD), Health Literacy on the Practice of Physical Activities among Diabetics (HLPPA - D), and Health Literacy regarding Drug Adherence among Diabetics (HLDA-D). Sociodemographic and biochemical profile was also evaluated. Spearman correlation was used (p < 0.05). Results: 187 individuals with DM were included. Regarding laboratory analyses, insulin dosage had a mean value of 12.3 microUI/mL (SD: ±15.7), mean blood glucose was 148.1 mg/dl (SD: ±59.7) and mean HbA1c was 7.54 % (SD: ±1.8). In the correlation analysis, higher age and lower income were weakly correlated with lower cognitive level. No correlation was identified for biochemical variables and cognitive condition. A positive and weak correlation between cognition and HL was observed in the studied population. Conclusions: In older people living with DM the cognitive condition is correlated to specific topics of HL (nutritional status, physical activity and medication adherence).